(untitled) (Bangladesh Journal of Botany, 2019)
To support the crop improvement of Physalis ixopcarpa Brot., 16 accessions provided by National Plant Germ Plasm System USDA (USA) and one recently reported accession from Pakistan were characterized for morphometric and genetic diversity. These accessions were evaluated for morphometric and physiological traits. Among these traits, plant height, relative water content, total chlorophyll content, per cent germination and leaf area were found as best for the differentiation among these accessions. These accessions were also screened for genetic differentiation using RAPDs primers. The genetic similarity among accessions was in the range of 0.03 to 0.33. The RAPD data supported the ecological distribution of accessions. It is inferred from molecular typing that accessions PI512005 and PI360740 were the most diverse accessions among the accessions of P. ixocarpa. In this study the genetic data were deviated from morphometric data which might be due to the qualitative and quantitative characteristics of accessions influenced by environmental factors.